The Role of Electronic Word of Mouth and Brand Image in Purchase Decisions for The Miracle Mates Brand on Tokopedia - Henny Utarsih; Helmy Deliana Putra (Journal of Accounting, Management, Economics, and Business (ANALYSIS), 2026)
Purpose – This study aims to examine the role of Electronic Word of Mouth and Brand Image in influencing consumer Purchase Decisions for the Miracle Mates brand on Tokopedia. The study is based on the growing importance of online reviews, digital consumer opinions, and brand perception in shaping purchasing behavior in e-commerce, particularly in the local fashion industry. Methodology – This research used a quantitative method with descriptive and verificative approaches. The sample consisted of 100 Miracle Mates consumers selected using non-probability sampling with a purposive sampling technique. Data were collected through questionnaires and analyzed using descriptive analysis, validity and reliability tests, classical assumption tests, multiple linear regression, correlation analysis, coefficient of determination, t-test, and F-test. Findings – The results show that Electronic Word of Mouth and Brand Image are categorized as good, while Purchase Decision is categorized as less good. Partially and simultaneously, Electronic Word of Mouth and Brand Image have a significant influence on Purchase Decision. The coefficient of determination shows that both variables explain 15.6% of Purchase Decision, while the remaining 84.4% is influenced by other factors outside this study. Novelty – This research contributes by examining the combined role of Electronic Word of Mouth and Brand Image in purchasing decisions for a local fashion brand on Tokopedia. Significance – This study benefits Miracle Mates, digital marketers, e-commerce sellers, and future researchers in consumer behavior and digital marketing.